Pour une autre lecture de la guerre de Gaza - Jean-François Legrain (EchoGéo, 2009)
This article is an attempt to explore new schemes for the full understandig of what was the challenge in the last war in Gaza’s Strip. Between December 27th and January 21st nothing less than 1330 people died while 5450 others remained injuried on the Palestinian side. Ten Israeli soldiers and three civilians died in the meantime. This article is an interpretation of the Israeli way of managing the image of the Palestinian resistance movment in years, through the Muslim Brothers, FATHA, and now Hamas, as a danger for democracy and the western world. The figure of the trouble maker is used in order to justify a long term conflict which end Israel is the only country capable to put an end to.